The use of Acellular Dermal Matrices in the Management of Complex Traumatic Wounds in a Paediatric Population - Pillay, Kamlen (Division of Plastic and Reconstructive Surgery, 2021)
Introduction Complex soft tissue injuries are common in children. Paediatric wounds associated with large soft tissue defects pose a surgical challenge. This often necessitates extensive reconstructive surgery and frequently requires the use of microvascular free flaps. Local, regional and free flap surgery in children poses several challenges related to donor site morbidity, flap failure and the long-term sequelae of repeated surgeries for flap modification in a growing child. The introduction of acellular dermal matrices (ADM's) in recent decades has dramatically influenced the management of complex soft tissue wounds. The dermis in skin represents the functional aspect of skin. ADM's represent dermal structures artificially, hence their incorporation into the wound should restore skin characteristics specifically pliability. Some authors believe that ADM's have improved prognosis and reduced morbidity in the treatment of open wounds. Combining the use of ADM's together with split-thickness skin grafting (SSG) is rapidly becoming an important method used to manage such complex wounds. In this study, we explore whether the use of this technique has been a beneficial addition to the traditional management armamentarium for complex injuries in the extremities and report the rate of complications experienced by our patients at our paediatric hospital in Cape Town. Objective This study reviewed the number of complications experienced with the use of ADM's in treating complex wounds on the extremities of children. It includes 54 children treated between the years 2011 and 2016 at a national paediatric hospital. Methodology A retrospective folder review of children treated at our hospital between the years 2011 and 2016 with extremity injuries was conducted. A total of 189 patient folders were reviewed. Children (n= 54) with complex wounds in their extremities who had received an ADM were included in this study. Both short and long-term complications were identified. The patient age range was six months - 12 years, while the mean patient follow-up period was 390 days. Results All patients treated with ADMs for traumatic extremity injuries during this period were included in the study, irrespective of age or co-morbidities. In 45 patients the ADM and SSG healed without any complication that is, not requiring revision surgery at 1 year follow up. Seven patients who did not receive postoperative splinting and occupational / physiotherapy displayed wound contractures, requiring further reconstructive surgery, 4 of which were also in the group who experienced complete ADM or graft loss below. Six patients experienced complete loss of the ADM due to infection, which led to graft failure, requiring revision surgery. Of the six patients that experienced complete loss of the ADM, five were not treated with NPWT dressings. Noteworthy, is that all 45 patients who healed without any complication were treated with NPWT dressings. Biopsies that were performed on 18 patients at 2 weeks post application of the ADM, showed only granulation tissue. No evidence of residual ADM or accessory dermal structures was found in any of the samples, which were obtained from multiple loci of the ADM in situ. The mean time to closure with this method was 3 weeks and the mean hospital stay was 26 days. Two patients were lost to follow-up and were excluded from the morbidity analysis arm of the study. Discussion We found that post-operative physiotherapy, occupational therapy and splinting are extremely important in preventing morbidity in particular scar contracture when associated with wounds treated with ADMs. There was no histological evidence to suggest that the ADM remains intact after 2 weeks post application. Our data reveals that vacuum assisted closure is a vital adjunct to this method, ensuring adequate ADM and graft take. Conclusion Complex wounds in the extremities of children pose a reconstructive dilemma to the plastic surgeon. In anatomically sensitive areas where traditional plastic surgery options are unavailable or undesirable, the use of ADMs and SSGs represent a realistic alternative for the reconstruction of large wounds associated with complex soft tissue injuries in the extremities of children.